Study of Petrogenesis Andesite Rock in Bualemo Region, North Gorontalo Regency Based on XRF Geochemistry Analysis - Fandji Marfian; Aang Panji Permana; Noviar Akase (Jambura Geoscience Review, 2023)
The research area is Bualemo Village, Kwandang District, North Gorontalo Regency. With coordinates 0˚ 47' 10" - 0˚ 48' 40" North Latitude and 122˚ 55' 0" - 122˚ 57' 5" East Longitude with an area of about 10 km2. This study aims to determine the petrogenesis of andesite rocks and the tectonic setting in the study area. The method used in this study is a mapping method to determine the geological conditions of the research site and X-ray fluorescence (XRF) geochemical analysis to determine the chemical content of rocks. The results showed that the stratigraphy of the study area, sorted from oldest to youngest, was an andesite unit, an altered andesite unit, and an alluvial deposit unit. The geological structure in the study area is a tension joint with a general direction of relative north-south. The tension joint structure data analysis results have a value of N 171oE/79o. Based on geochemistry results, it was found that the type of magma is tholeiitic, with its name basalt and basaltic trachyte andesite. The origin of the magma is island arc tholeiitic and island arc calc-alkaline basalt, with the tectonic setting of the study area being subduction between two oceans, namely between the Sulawesi sea plate and the Sula plate.